Prolonged Use of Ertapenem to Treat Infected Diabetic Foot Ulcers - Ashwin Algudkar; Gidon Ellis; Fareeduddin Ahmad; Hilary Tindall (Case Reports in Medicine)
We present the case of a diabetic man who was successfully treated with ertapenem for over 4 months for severe infection of his foot ulcers. After initial unsuccessful treatment with empirical intravenous antibiotics, ertapenem was started on microbiology advice and led to a marked improvement in the soft-tissue infection. Ertapenem was continued for a total of 137 days under close clinical and biochemical monitoring and produced a complete resolution of the foot infection. This is the first documented case that we know of in which ertapenem has been safely used for this duration of time.